Psychiatric nursing - Keltner, Norman L.,author; Schwecke, Lee Hilyard, author; Bostrom, Carol E.,author (St. Louis : Mosby/Elsevier, 2007)
Accompanying CD-ROM contains extra learning activities, study tools, an audio glossary, interactive exercises, neurology review, and review questions.
Introduction to psychiatric nursing -- Psychotherapeutic management in the continuum of care -- Continuum of care -- Models for working with psychiatric patients -- Legal issues -- Psychobiologic bases of behavior -- Nurse-patient communication -- Nurse-patient relationship -- Nursing process -- Stress, anxiety, coping, and crisis -- Working with the aggressive patient -- Working with groups of patients -- Working with the family -- Cultural competence in psychiatric nursing -- Spirituality -- Introduction to psychotropic drugs -- Antiparkinsonian drugs -- Antipsychotic drugs -- Antidepressant drugs -- Antimanic drugs -- Antianxiety drugs -- Antidementia drugs -- Introduction to milieu management -- Variables affecting the therapeutic environment -- Therapeutic environment in various treatment settings -- Special environments: forensic psychiatric treatment settings -- Introduction to psychopathology -- Schizophrenia and other psychoses -- Depression -- Bipolar disorders -- Anxiety-related, somatoform, and dissociative disorders -- Cognitive disorders -- Personality disorders -- Sexual disorders -- Substance-related disorders -- Dual diagnosis -- Eating disorders -- Behavior therapies -- Somatic therapies -- Alternative and complementary therapies -- Survivors of violence and trauma -- Child and adolescent psychiatric nursing -- Mental disorders in older adults.
Includes bibliographical references and index.
Keywords: Psychiatric nursing; Psychotherapy; Nurse and patient